ZIF-8-coated Cu-BTCMOF composite material as well as preparation method and application thereof
By loading the zinc-based metal organic frame with ZIF-8@Cu-BTCMOF composite material on the copper-based metal organic frame, the problem of poor water stability of existing adsorbents is solved, and the adsorption capacity of iodine is significantly improved. It is suitable for removing smoke from nuclear power plants. Volatile iodine in the gas.
Patent Information
- Application Number
- CN202411564696.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2024-12-27
AI Technical Summary
The existing adsorbents have poor water stability when removing volatile iodine in the flue gas of nuclear power plants, which limits their application, especially copper MOFs are easily invaded by moisture, resulting in limited adsorption capacity.
Using ZIF-8@Cu-BTCMOF composite material, this material improves water stability and enhances iodine adsorption capacity by loading zinc-based metal organic frames on the surface of copper-based metal organic frames. By controlling the production amount of copper and zinc, it further Optimize adsorption performance.
High stability in aqueous solution and improved iodine ion adsorption capacity, significantly improved the adsorption efficiency of iodine, and was suitable for removing radioactive iodine waste gas flow from nuclear fuel processing.
Smart Images

Figure CN119186524A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorbents, and in particular to a ZIF-8@Cu-BTCMOF composite material and a preparation method and application thereof. Background Art
[0002] Rapid global population growth, coupled with industrial growth, has amplified energy demand. Traditional energy sources, such as fossil fuels, solar and wind, play an important role in maintaining the balance. But it is vital to explore alternative energy options to sustainably meet this escalating demand. Nuclear power has proven to be a reliable and abundant energy source. However, it does come with significant complexities, especially radioactive waste.
[0003] Among the various iodine isotopes, 129 I and 131 I has attracted particular attention. Isotopes 129 I has a long lifetime, with a half-life of 15.2 million years; it can easily migrate through our environment and accumulate in organisms. 131 I has a short lifespan but emits high levels of radiation. 131 I can enter the human body through inhalation or ingestion, posing serious health risks. Iodine is highly volatile and easily evaporates, and is mainly found in the flue gas of nuclear power plants. Therefore, there is an urgent need for effective adsorbents to efficiently remove radioactive iodine from the waste gas streams generated during nuclear fuel processing.
[0004] Although various adsorbents have been developed to capture volatile iodine, including activated carbon, zeolites, metal organic frameworks (MOFs), graphene-based materials, aerogels, carbon-based polymers, and layered double hydroxides, copper MOFs have good iodine adsorption capacity, but their application is limited due to their susceptibility to water intrusion and poor water stability. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a ZIF-8@Cu-BTCMOF composite material and a preparation method and application thereof. The composite material of the present invention has good water stability and also has good iodine adsorption capacity.
[0006] The invention provides a ZIF-8@Cu-BTCMOF composite material. The structure of the ZIF-8@Cu-BTCMOF composite material is that a zinc-based metal organic framework is loaded on the surface of a copper-based metal organic framework.
[0007] The present invention also provides a preparation method of the ZIF-8@Cu-BTCMOF composite material, which comprises: dissolving a copper-based metal organic framework, zinc nitrate hexahydrate, and polyvinyl pyrrolidone (PVP) in methanol, and mixing them uniformly; adding a methanol solution containing 2-methylimidazole, stirring, solid-liquid separation, washing, and drying.
[0008] Furthermore, the mass ratio of the copper-based metal organic framework, zinc nitrate hexahydrate, and polyvinyl pyrrolidone is 0.5 parts: 0.04 parts: 0.2 parts to 0.6 parts.
[0009] Furthermore, the mass ratio of the copper-based metal organic framework, zinc nitrate hexahydrate, and polyvinyl pyrrolidone is 0.5 parts: 0.04 parts: 0.6 parts.
[0010] Furthermore, the mass concentration of the copper-based metal organic framework in methanol is 0.5 g / 30 mL.
[0011] Furthermore, there are many ways to achieve uniform mixing. As an example, ultrasound can be performed for 5-8 minutes, and then stirring can be performed at a rotation speed of 200 rpm for 1 hour.
[0012] Furthermore, in the methanol solution containing 2-methylimidazole, the mass concentration of 2-methylimidazole is 0.54 g / 30 mL.
[0013] Furthermore, the volume ratio of the uniformly mixed solution to the methanol solution containing 2-methylimidazole is 1:1.
[0014] Furthermore, the specific method of washing includes washing with methanol at least three times.
[0015] Furthermore, the drying temperature is 70° C.-90° C. In the present invention, the drying time is not specified, and those skilled in the art can adjust it according to actual needs.
[0016] Furthermore, the preparation method of the copper-based metal organic framework includes: The polyvinyl pyrrolidone is dissolved and dispersed in anhydrous ethanol, 1,3,5-benzenetricarboxylic acid is added, mixed evenly, and then an ethanol solution containing copper nitrate trihydrate is added, hydrothermal reaction is carried out, cooling, solid-liquid separation, washing, and drying are carried out.
[0017] Furthermore, the mass concentration of the polyvinyl pyrrolidone in anhydrous ethanol is 0.4477 g / 50 mL.
[0018] Furthermore, the mass concentration of the 1,3,5-benzenetricarboxylic acid in anhydrous ethanol is 0.8 g / 50 mL.
[0019] Furthermore, the uniform mixing may be performed by stirring. As an example, the stirring time is 30 minutes.
[0020] Furthermore, in the ethanol solution containing copper nitrate trihydrate, the mass concentration of copper nitrate trihydrate is 1.64 g / 50 mL.
[0021] Furthermore, in the ethanol solution, the volume ratio of anhydrous ethanol to deionized water is 1:1.
[0022] Furthermore, the volume ratio of the uniformly mixed solution to the ethanol solution containing copper nitrate trihydrate is 1:1.
[0023] Furthermore, sufficient stirring may be performed before the hydrothermal reaction to facilitate the hydrothermal reaction. As an example, stirring is performed at a rotation speed of 250 rpm for 1 hour.
[0024] Furthermore, the temperature of the hydrothermal reaction is 115°C-125°C, and the reaction time is 19h-21h.
[0025] Furthermore, the specific method of washing includes: washing with deionized water and ethanol for 3-5 times in sequence, and then washing with anhydrous alcohol at 60°C.
[0026] Furthermore, the drying temperature is 55° C.-65° C., and the drying time is 18-22 hours.
[0027] The present invention also provides application of the ZIF-8@Cu-BTCMOF composite material in adsorbing iodide ions.
[0028] The embodiments of the present invention have the following technical effects: 1. In the present invention, a layer of zinc-based metal-organic framework structure is loaded on the copper-based metal-organic framework. On the one hand, the zinc-based metal-organic framework can improve the stability of the copper-based metal-organic framework in aqueous solution, thereby having the iodine adsorption capacity of the copper-based metal-organic framework. On the other hand, the zinc-based metal-organic framework can also further increase the space for physical adsorption of iodine ions, which is conducive to further improving the iodine ion adsorption capacity.
[0029] 2. In the present invention, the generation amount of the copper-based metal organic framework and the zinc-based metal organic framework is further controlled, so that on the basis of ensuring the improvement of the copper-based metal organic framework, the adsorption capacity of the composite material finally obtained for iodine is also guaranteed. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 is a microscopic diagram provided by the embodiments and comparative examples of the present invention, wherein Figure 1 A in the figure is the SEM picture of comparative example 1. Figure 1 B is the SEM picture of comparative example 2. Figure 1 C is the SEM image of Example 1, Figure 1 D in is the SEM picture of Example 2, Figure 1 E in FIG. is the SEM image of Example 3.
[0032] Figure 2 is the test result after iodine adsorption in Example 3 of the present invention, wherein Figure 2 A in the figure is the EDS image after iodine adsorption in Example 3. Figure 2 B is the SEM image of Example 3 after iodine adsorption. Figure 2 b-1 is the C element distribution diagram after iodine adsorption in Example 3, Figure 2 b-2 is the distribution diagram of I element after iodine adsorption in Example 3, Figure 2 b-3 is the distribution diagram of O element after iodine adsorption in Example 3. Figure 2 b-4 is the Zn element distribution diagram after iodine adsorption in Example 3, Figure 2 b-5 is the N element distribution diagram after iodine adsorption in Example 3, Figure 2 b-6 is the Cu element distribution diagram after iodine adsorption in Example 3. Figure 2 C is the EDS morphology diagram of Example 3 after iodine adsorption. Figure 2 C-1 is the mass percentage of each element after iodine is adsorbed in Example 3.
[0033] Figure 3 is a Fourier transform infrared spectra of the embodiment and the comparative example before and after iodine adsorption, wherein Figure 3 a is a Fourier transform infrared spectrum of the embodiment and the comparative example before iodine adsorption, Figure 3 Middle b is the Fourier transform infrared spectra of the embodiment and comparative example after iodine adsorption.
[0034] Figure 4 is the XRD diagram of the embodiment and the comparative example before and after iodine adsorption, wherein Figure 4 a is the XRD diagram of the embodiment and the comparative example before iodine adsorption, Figure 4 b is the XRD diagram of the embodiment and comparative example after iodine adsorption.
[0035] Figure 5 are nitrogen adsorption and desorption isotherms of Examples and Comparative Examples.
[0036] Figure 6 is the thermogravimetric analysis result before and after iodine adsorption in Example 3, wherein Figure 6 a is the thermogravimetric analysis of Example 3 before iodine adsorption, Figure 6 Figure b is the thermogravimetric analysis of Example 3 after iodine adsorption.
[0037] Figure 7 is the XPS analysis before iodine adsorption in Example 2, wherein Figure 7 The a in the figure is a high-resolution image of C 1s. Figure 7 The b in the middle is a high-resolution image of O1s. Figure 7 The c in the figure is a high-resolution image of N 1s. Figure 7 (d) is a high-resolution image of Cu 2p. Figure 7 (e) is a high-resolution image of Zn2p.
[0038] Figure 8 is the XPS analysis after iodine adsorption in Example 2, wherein Figure 8 a in the middle is a high-resolution image of each element. Figure 8 (b) is a high-resolution image of I 3d.
[0039] Fig. 9 is the test result of capturing iodine in the embodiment and the comparative example, wherein Fig. 9 Figure A is a diagram of the iodine capture method by gravimetric measurement. Fig. 9 B is the weight change of iodine adsorption capacity of the examples and comparative examples with time at 353.15K.
[0040] Fig.10 is a test of iodine adsorption in the embodiments and comparative examples, wherein Fig.10 a is the time-varying kinetic adsorption of the examples and comparative examples in iodine / cyclohexane solution, Fig.10 b is the isotherm of the adsorbent in 20 mL iodine / cyclohexane solvent for 20 hours. Fig.10 In c, pseudo-first-order kinetic model and pseudo-second-order kinetic model, Fig.10 The two models in d are Langmuir model and Freundlich model.
[0041] Fig.11 The effect of pH on iodine adsorption in Example 1 is shown in FIG.
[0042] Fig.12 The adsorption-desorption cycle test of Example 3, wherein Fig.12 a is the test result. Fig.12 Part b is the physical picture corresponding to the test result.
[0043] Fig.13 This is a high-resolution image of Zn 2p after iodine adsorption in Example 2. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0045] In a first aspect, some embodiments of the present invention provide a ZIF-8@Cu-BTCMOF composite material, wherein the structure of the ZIF-8@Cu-BTCMOF composite material is a copper-based metal organic framework with a zinc-based metal organic framework loaded on its surface.
[0046] In the composite material obtained by the present invention, the zinc-based metal organic framework can not only improve the stability of the copper-based metal organic framework in aqueous solution, thereby having the iodine adsorption capacity of the copper-based metal organic framework, but the zinc-based metal organic framework can also further increase the space for physical adsorption of iodine ions, thereby facilitating further improvement of the iodine ion adsorption capacity. In the second aspect, some embodiments also provide a method for preparing the ZIF-8@Cu-BTCMOF composite material, which comprises: dissolving a copper-based metal organic framework, zinc nitrate hexahydrate, and polyvinyl pyrrolidone (PVP) in methanol and mixing them evenly; adding a methanol solution containing 2-methylimidazole, stirring, solid-liquid separation, washing, and drying.
[0047] In the method of the present invention, polyvinyl pyrrolidone is used as a surfactant, which not only promotes the dispersion of the copper-based metal organic framework and enhances the absorption of iodine through its porous structure, but also is used to connect the zinc-based metal organic framework and the copper-based metal organic framework.
[0048] In some embodiments, the mass ratio of the copper-based metal organic framework, zinc nitrate hexahydrate, and polyvinyl pyrrolidone is 0.5 parts: 0.04 parts: 0.2 parts-0.6 parts.
[0049] In some embodiments, the mass ratio of the copper-based metal organic framework, zinc nitrate hexahydrate, and polyvinyl pyrrolidone is 0.5 parts: 0.04 parts: 0.6 parts.
[0050] In some embodiments, the mass concentration of the copper-based metal organic framework in methanol is 0.5 g / 30 mL.
[0051] In some embodiments, there are many ways to achieve uniform mixing. As an example, ultrasound may be performed for 5-8 minutes, and then stirring may be performed at a rotation speed of 200 rpm for 1 hour.
[0052] In some embodiments, in the methanol solution containing 2-methylimidazole, the mass concentration of 2-methylimidazole is 0.54 g / 30 mL.
[0053] In some embodiments, the volume ratio of the uniformly mixed solution to the methanol solution containing 2-methylimidazole is 1:1.
[0054] In some embodiments, the specific method of washing includes washing with methanol at least three times.
[0055] In some embodiments, the drying temperature is 70° C.-90° C. In the present invention, the drying time is not specified, and those skilled in the art can adjust it according to actual needs.
[0056] In some embodiments, the method for preparing the copper-based metal organic framework includes: The polyvinyl pyrrolidone is dissolved and dispersed in anhydrous ethanol, 1,3,5-benzenetricarboxylic acid is added, mixed evenly, and then an ethanol solution containing copper nitrate trihydrate is added, hydrothermal reaction is carried out, cooling, solid-liquid separation, washing, and drying are carried out.
[0057] In some embodiments, the mass concentration of polyvinyl pyrrolidone in anhydrous ethanol is 0.4477 g / 50 mL.
[0058] In some embodiments, the mass concentration of 1,3,5-benzenetricarboxylic acid in anhydrous ethanol is 0.8 g / 50 mL.
[0059] In some embodiments, the uniform mixing may be performed by stirring. As an example, the stirring time is 30 minutes.
[0060] In some embodiments, the mass concentration of copper nitrate trihydrate in the ethanol solution containing copper nitrate trihydrate is 1.64 g / 50 mL.
[0061] In some embodiments, in the ethanol solution, the volume ratio of anhydrous ethanol to deionized water is 1:1.
[0062] In some embodiments, the volume ratio of the uniformly mixed solution to the ethanol solution containing copper nitrate trihydrate is 1:1.
[0063] In some embodiments, sufficient stirring may be performed before the hydrothermal reaction to facilitate the hydrothermal reaction. As an example, stirring is performed at a rotation speed of 250 rpm for 1 hour.
[0064] In some embodiments, the temperature of the hydrothermal reaction is 115° C.-125° C., and the reaction time is 19 h-21 h.
[0065] In some embodiments, the specific method of washing includes: washing with deionized water and ethanol for 3-5 times in sequence, and then washing with anhydrous alcohol at 60°C.
[0066] In some embodiments, the drying temperature is 55° C.-65° C., and the drying time is 18-22 hours.
[0067] In a third aspect, some embodiments of the present invention also provide the use of the ZIF-8@Cu-BTCMOF composite material in the adsorption of iodine ions.
[0068] The present invention further prepared embodiments and comparative examples for further comparison: Embodiment 1: Step 1: PVP (model: K30, 0.4477 g) was dispersed and dissolved in anhydrous ethanol (50 mL) at 25 °C and stirred at 200 rpm for 30 minutes. Then 0.8 g (3.8 mmol) of 1,3,5-benzenetricarboxylic acid was added to the PVP solution at room temperature and stirred for 30 minutes, which is solution A. Next, 1.64 g (6.8 mmol) of copper nitrate trihydrate was dissolved in a mixture of ethanol / water (v / v=1:1) (50 mL) under continuous stirring for 30 minutes until it was completely dissolved, which is solution B. Next, the prepared solutions (A+B) were mixed and stirred at 250 rpm for 1 hour at room temperature. Finally, the mixture was transferred to a 100 mL stainless steel autoclave at 120 °C for 20 hours and then cooled naturally at room temperature. The obtained blue powder sample was separated by filtration or centrifugation and washed with deionized water and ethanol 3-5 times. It was further washed with anhydrous alcohol at 60 °C overnight. The Cu-MOF was dried in a vacuum oven at 60 °C for 20 h; Step 2: 0.50 g of the copper-based metal organic framework obtained in step 1, 0.04 g of PVP and 0.20 g of zinc nitrate hexahydrate were placed in 30 mL of methanol solution, ultrasonically treated for 5-8 minutes to form solution A, and stirred at 200 rpm for 1 hour. Solution B was prepared by adding 30 mL of methanol and 0.54 g of 2-methylimidazole and stirring for 1 hour. Solution B was mixed into solution A and then stirred at room temperature for 3 hours. The powder product was filtered, centrifuged, washed with methanol, and vacuum dried at 80 ° C to obtain a composite material, recorded as ZIf-8@Cu-BTC / 0.2.
[0069] Embodiment 2: The method of Example 2 is the same as that of Example 1, except that the amount of zinc nitrate hexahydrate added in Example 2 is 0.4 g, and the rest is the same as that in Example 1, which is recorded as ZIf-8@Cu-BTC / 0.4.
[0070] Embodiment 3: The method of Example 3 is the same as that of Example 1, except that the added amount of zinc nitrate hexahydrate in Example 3 is 0.6 g, and the rest is the same as that of Example 1, which is recorded as ZIf-8@Cu-BTC / 0.6.
[0071] Comparative Example 1: PVP (model: K30, 0.4477 g) was dispersed and dissolved in anhydrous ethanol (50 mL) at 25 °C and stirred at 200 rpm for 30 minutes. Then 0.8 g (3.8 mmol) of 1,3,5-benzenetricarboxylic acid was added to the PVP solution at room temperature and stirred for 30 minutes, which is solution A. Next, 1.64 g (6.8 mmol) of copper nitrate trihydrate was dissolved in a mixture of ethanol / water (v / v=1:1) (50 mL) under continuous stirring for 30 minutes until it was completely dissolved, which is solution B. Next, the prepared solutions (A+B) were mixed and stirred at 250 rpm for 1 hour at room temperature. Finally, the mixture was transferred to a 100 mL stainless steel autoclave at 120 °C for 20 hours and then cooled naturally at room temperature. The obtained blue powder sample was separated by filtration or centrifugation and washed with deionized water and ethanol 3-5 times. It was further washed with anhydrous alcohol at 60 °C overnight. The copper-based metal-organic framework was dried in a vacuum oven at 60 °C for 20 h and was recorded as Cu-BTC.
[0072] Comparative Example 2: Zinc nitrate hexahydrate (10 mmol, 2.975 g) was dissolved in 50 mL of methanol and marked as solution A. 2-Methylimidazole (50 mmol, 4.205 g) was dissolved in 50 mL of methanol and marked as solution B. After uniform dispersion, solution B was quickly poured into solution A. The mixed solution was then transferred into a 150 mL round-bottom flask, which was then sealed and stirred at 25 °C for 3 hours. The solution was aged at room temperature for 24 hours. A white solid precipitate was obtained by centrifugation at 8000 rpm, repeatedly washed with a methanol solution, and vacuum dried at 80 °C overnight. It was marked as ZIF-8.
[0073] The embodiments and comparative examples were tested in the present invention, and the testing method is as follows: (1) Gaseous iodine capture: To reduce and handle radioactive iodine ( 131 I and 129 I) Risks associated with the present invention using non-radioactive 127 I 2) as a substitute. The iodine vapor absorption experiment was conducted by gravimetric analysis. About 100 mg of Cu-BTC and its composite sample of the present invention were placed in an open heat-resistant plastic container. Excess iodine solid (3 grams) was added to the container, which was then sealed. The container was heated to 80°C under ambient pressure.
[0074] The composite samples of the examples after iodine adsorption after the specified duration were cooled to room temperature and weighed. The containers were then removed at different time intervals and the weight was recorded after each cooling period. To ensure the repeatability of the experiments, each experiment was performed three times and the average results were analyzed: ; Where Q e is the iodine absorption, m i and m f The examples are samples before and after iodine adsorption (mg / g).
[0075] (2) Adsorption of iodine in solution: An iodine solution with an initial concentration of 1000 mg / L was prepared by dissolving an accurately measured amount of iodine in cyclohexane. Experimental solutions of different iodine concentrations (100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L and 500 mg / L) were obtained by serial dilution of the stock solution. A predetermined amount of adsorbent 10 mg was added to the iodine solution (20 mL). The mixture was then stirred in a thermostatic oscillator at a constant speed of 150 rpm for different time intervals. After the adsorption process, the adsorbent was separated from the solution using a handheld magnet. The concentration of residual iodine in the solution was determined spectrophotometrically at a wavelength (523 nm) using a UV-Vis spectrophotometer. The adsorption capacity of the adsorbent for iodine was calculated using the following equation: ; Where Q i (mg / g) is the iodine adsorption capacity, C 0 is the initial concentration of iodine solution (mg / L), C e is the concentration of iodine solution after adsorption, V is the volume of iodine solution (L), and M is the mass of adsorbent (g). The above experiment was repeated three times for each set of data, and the average value was taken.
[0076] (3) Kinetic adsorption study: 10 mg of the adsorbent was added to a 50 mL container containing 20 mL of a 200 mg / L iodine solution. The mixture was mechanically stirred at 25°C. At different time intervals, 5 mL aliquots were taken out and the adsorbent was separated by filtration. The concentration of molecular iodine in the remaining solution was determined by UV spectrophotometry.
[0077] (4) Adsorption isotherm: To establish the iodine adsorption isotherm, a series of iodine solutions with different initial concentrations (100 mg / L-500 mg / L) were prepared in increments of 100 mg / L. The pH of each solution was maintained at 7. A fixed amount of adsorbent (10 mg) was added to 20 mL of each iodine solution. The mixture was mechanically stirred at room temperature (25 °C) for 12 h. The iodine concentration in the solution was subsequently measured using a UV-Vis spectrophotometer at a wavelength of 523 nm.
[0078] (5) Effect of pH value: The experiments were performed by adjusting the pH of each sample using aqueous HCl or NaOH as a strong acid or base, respectively. Subsequently, the samples were shaken at 150 rpm for 4 h at 25 °C. After the 4-h adsorption period, the solutions were centrifuged and the iodine adsorption capacity was evaluated.
[0079] (6) Iodine release / adsorbent regeneration: I 2 The loaded ZIf-8@Cu-BTC nanocomposite was placed in an ethanol solution (10 mL) and allowed to release a set amount for 16 hours. Ethanol is a versatile solvent with a strong solvating capacity for a wide range of molecules. In order to effectively solvate and subsequently remove ethanol from the adsorbent, a simple and effective method is to soak the adsorbent in a large amount of ethanol. Images of the desorption experiment at different times were taken to monitor the level of iodine released from the sample.
[0080] Results and Analysis: Table 1 Comparison of adsorption capacity of examples and comparative examples
[0081] Scanning electron microscopy (SEM) analysis Figure 1 (A)- Figure 1 (B) shows the unique morphology of Comparative Example 1 and Comparative Example 2, respectively. Figure 1 (A) Cu-BTC crystals are regular octahedral in shape, with a particle size of about 3 µm. Figure 1 (B) The ZIF-8 particles have a rhombic dodecahedral structure and a particle size of about 100 nm.
[0082] With the increase of the addition amount of zinc nitrate hexahydrate, the coverage of ZIF-8 particles on the Cu-BTC surface becomes more extensive, e.g. Figure 1 (C)- Figure 1(E) When the amount of zinc nitrate hexahydrate added is small, the loading of ZIF-8 leads to incomplete coverage, which may cause incomplete improvement of the copper-based metal organic framework and poor water stability of the composite material; when the amount of zinc nitrate hexahydrate added is small, it leads to the formation of a multilayer structure and agglomeration of ZIF-8 particles, which may hinder mass transfer and iodine adsorption. Therefore, in the present invention, the mass ratio of the copper-based metal organic framework to zinc nitrate hexahydrate is 0.5 parts: 0.2 parts to 0.6 parts.
[0083] Taking Example 3 as an example, Example 3 was characterized after adsorbing iodine. Figure 2 shown. Figure 2 The SEM in (B) shows that Example 3 maintains an octahedral structure with minimal edge damage. Figure 2 (b-1)- Figure 2 (b-6) respectively shows the distribution of C element, I element, O element, Zn element, N element, and Cu element in Example 3 of iodine adsorption, which not only verifies the adsorption effect of the present invention on iodine, but also proves that the zinc-based metal-organic framework is coated on the copper-based metal-organic framework. Figure 2 (C) shows Figure 2 (A) EDS spectrum of the area shown, Figure 2 The EDS spectrum in (C-1) shows that the maximum adsorption of iodine by the composite material is about 31.4% of the total weight.
[0084] Fourier transform infrared spectroscopy was performed to identify the functional groups in the prepared samples, e.g. Figure 3 shown. Figure 3 The spectra in FIG. 1 show characteristic peaks of the embodiments and comparative examples. The peaks of the embodiments and comparative examples are 1645 cm -1 、1620cm -1 、1556cm -1 、1448cm -1 、1372cm -1 、1311cm -1 、1107cm -1 、996cm -1 、763cm -1 、730cm -1 、725cm -1 、484cm -1 、423cm -1 、1150cm -1 and 996cm -1 It is noteworthy that these peak positions remain unchanged before and after iodine adsorption, indicating that there are little structural changes in the complex.
[0085] The specific functional groups were identified based on their corresponding peak positions, such as at 1645 cm -1Cu-BTC carboxylic acid (-COOH) stretched at 1372 cm -1 The hydroxyl (-OH) plane bends at 1107 cm -1 and 725cm -1 Cu-OC stretching can be seen at 3380cm -1 -3460cm -1 The absorption peak at 1372cm belongs to the stretching of interlayer water molecules. -1 and 1448cm -1 The absorption peak at 1645 cm corresponds to the stretching of the aromatic ring, while the asymmetric stretching of 1,3,5-benzenetricarboxylic acid can be attributed to the peak at 1645 cm -1 and 1620cm -1 . Absorbance at 763cm -1 and 730cm -1 The peak is at 423 cm, which corresponds to the Cu chelation of the OC=O group in MOF. The ZIF-8 peak can be expressed as 423 cm -1 The absorption peak at 1556 cm corresponds to the Zn-N stretching mode. -1 The stretching bands at 1150 cm-1 and the imidazole ring -1 and 996cm -1 The (CN) stretching and bending at 2930 cm-1 indicate the intensity of ZIF-8 and (CH) at 2930 cm-1, respectively. -1 and 3135cm -1 These characteristic peaks indicate that the structural integrity of the two components is maintained after iodine adsorption in the examples.
[0086] XRD analysis was used to study the crystal structure of the prepared composites. Figure 4 The diffraction patterns shown show characteristic peaks corresponding to the various components. For Cu-BTC, characteristic peaks were observed at 6.70°, 9.49°, 11.65°, 13.82°, 16.9°, 17.51°, 26.34°, 29.3°, and 34.4°, matching the previously reported values for the (200), (220), (222), (400), (422), (551), (440), (773), and (882) planes, respectively.
[0087] Likewise, in Figure 4 In (a), characteristic peaks of ZIF-8 were observed at 6.42°, 8.47°, 12.8°, 13.8°, 18.29°, and 22.31°, corresponding to the (011) crystal plane, (002) crystal plane, (112) crystal plane, (022) crystal plane, (013) crystal plane, and (222) crystal plane, respectively.
[0088] In the XRD spectrum, the characteristic peaks of ZIf-8@Cu-BTC / 0.2, ZIf-8@Cu-BTC / 0.4, ZIf-8@Cu-BTC / 0.6, Cu-BTC and ZIF-8 are clearly visible. It is worth noting that with the increase of ZIF-8 content in the composite material, the intensity of ZIF-8 (011), (002) and (112) crystal planes gradually increases, indicating that ZIF-8 is successfully loaded into the Cu-BTC framework. Figure 4 (b), after the adsorption of iodine in Example 1-Example 3 (ZIf-8@Cu-BTC / 0.2-I 2 、ZIf-8@Cu-BTC / 0.4-I 2 、ZIf-8@Cu-BTC / 0.6-I 2 ), the peak shift of the synthetic material confirms the adsorption of iodine in its available space and interstitial space.
[0089] In order to characterize the specific surface area and pore size distribution of the synthesized samples, nitrogen adsorption–desorption isotherms were determined, e.g. Figure 5 As shown. According to IUPAC classification, Figure 5 The isotherms shown show a combination of type I and type IV behavior, indicating the presence of both micropores and mesopores in the composite.
[0090] Taking Example 3 as an example, TGA was performed to evaluate the composite before and after iodine adsorption in Example 3. Figure 6 As shown. Figure 6 In (a), the sample shows a slight weight loss below 200 °C due to the removal of residual solvent and bound water. Figure 6 (a) shows that ZIf-8@Cu-BTC / 0.6 has excellent thermal stability (stable to 330°C), indicating that ZIf-8@Cu-BTC / 0.6 nanocomposites are very suitable for iodine vapor capture (150°C) in industrial applications; the total mass reduction of ZIf-8@Cu-BTC / 0.6 mainly occurs between 259°C and 441°C. Figure 6 In (b), the composite material after iodine adsorption shows three different weight loss stages in the same temperature range, with a final weight loss of 53%. It is worth noting that after iodine adsorption, the weight loss rate of the material relative to temperature decreases. The DTG curve also shows the change in the thermal stability of the material, such as Figure 6 (a)- Figure 6 (b), the image before adsorption shows that the sharper the curve, the more obvious the degradation of the composite material at (260-350) °C before adsorption. Interestingly, in our composite, two different degradation peaks can be seen before iodine adsorption, while a sharp and unique peak can be seen after iodine adsorption, which indicates the iodine adsorption and thermal stability of the material after the reaction.
[0091] Taking Example 3 as an example, the enhanced thermal stability of the ZIf-8@Cu-BTC composite compared to the original Cu-BTC sample, the significant weight loss observed at higher temperatures for the composite may be attributed to the protective effect of the ZIF-8 coating and the gradual decomposition of the organic ligands and the collapse of the material skeleton. A noteworthy observation is that, as Figure 6 As shown, there are differences in the weight loss curves between the organic ligand and the material framework, with the composite exhibiting two distinct sharp weight loss events totaling 79%. However, after iodine adsorption, the weight loss was reduced to 54%, suggesting that there may be an interaction between iodine and the composite that affects its thermal stability.
[0092] Taking Example 2 as an example, X-ray photoelectron spectroscopy (XPS) analyzed the composite material of Example 2. Figure 7 As shown. The XPS survey scan of the ZIf-8@Cu-BTC / 0.4 sample shows characteristic peaks corresponding to the Zn 2p, Cu 2p, O 1s, N 1s and C 1s elements. Figure 7 In (e), the high-resolution Zn 2p spectrum shows two distinct peaks with binding energies of 1045.02 eV and 1021.91 eV, respectively, which are attributed to Zn 2p 1 / 2 and Zn 2p 3 / 2 The observed spin-orbit separation of Zn 2p is 23.11 eV, which strongly suggests the presence of Zn 2+ ion. Figure 7 The N 1s spectrum of (c) shows a characteristic peak at a binding energy of 398.96 eV and a characteristic peak at 401.25 eV, which can be attributed to the nitrogen atom of 2-methylimidazole. Similarly, the C 1s spectrum Figure 7 (a) shows three consecutive peaks at 284.5 eV (CC), 285.5 eV (COC) and 287.8 eV (OC=O). O 1s spectrum Figure 7 (b) shows the peaks at 531.62 eV and 533.66 eV, which can be attributed to the oxygen atoms within the composite structure. The co-existence of these peaks confirms the ZIf-8@Cu-BTC composite.
[0093] Cu 2p spectrum Figure 7 (d) shows five prominent peaks of different intensities with binding energies of 934.88 eV, 940.22 eV, 944.07 eV, 954.92 eV, and 962.68 eV, which can be attributed to the Cu 2p 3 / 2 and Cu 2p 1 / 2 , indicating that Cu(OH) 2 and metallic Cu are present. Example 2 High-resolution XPS analysis after iodine adsorption, such as Figure 8 As shown. Figure 8 All characteristic peaks corresponding to Zn 2p, Cu 2p, O 1s, N 1s, and C 1s elements in (a) persist, while their binding positions change slightly. It is worth noting that the C 1s peak shifts slightly to 284.99 eV and 286.95 eV, indicating that the chemical environment around the carbon atom changes slightly; similarly, the O 1s and N 1s peaks show small changes in binding energy, and the adsorbed N 1s spectrum shows three different peaks at binding energies of 399.28 eV, 400.65 eV, and 402.30 eV, further confirming the existence of the MOF framework.
[0094] High-resolution Zn 2p spectrum after iodine adsorption Fig.13 Again, two distinct peaks are shown, with binding energies of 1046.42 eV and 1022.84 eV, respectively, which are attributed to the Zn 2p 1 / 2 and Zn 2p 3 / 2 , the spin-orbit separation of Zn 2p remains at 23.58 eV, indicating that Zn 2+ ions. It is noteworthy that the XPS spectrum obtained after iodine adsorption Figure 8 (a) shows the emergence of new peaks corresponding to I 3d, which are usually observed around 630 eV and 650 eV, respectively, which clearly confirms the adsorption of iodine by ZIf-8@Cu-BTC / 0.4 nanocomposite. The XPS results are consistent with the XRD analysis, and the high-resolution I 3d spectrum Figure 8 Further analysis of (b) shows three distinct peaks at binding energies of about 632 eV and 621 eV, corresponding to I3d 3 / 2 and I 3d 5 / 2 In addition, the peaks observed around 632.29 eV and 619.60 eV are attributed to I - species, while the peak at 621.15 eV can be attributed to I 2 molecular.
[0095] To evaluate the iodine capture capacity of ZIF-8@Cu-BTC composites, time-dependent adsorption experiments were performed using both gas and liquid phases. In a typical gas phase experiment, the composite was placed at 80 °C and filled with I 2 The steam chamber is filled with steam and the absorption capacity is measured by monitoring the weight of each sample until saturation is reached.
[0096] exist Fig. 9(B) After iodine adsorption in Examples 1 to 3, the composite materials showed significantly higher gaseous iodine adsorption capacity compared with pure Cu-BTC and ZIF-8. All samples showed a fast adsorption rate in the first 2-3 hours, indicating that the iodine adsorption rate was very fast; the adsorption capacity slowed down after 5-6 hours and reached equilibrium within 10 hours.
[0097] Compared with Examples 1-3, the equilibrium I of ZIF-8 2 The uptake was relatively low, at 1115.05 mg / g. 2 Adsorption capacity, I 2 The equilibrium adsorption capacities were 1291.14 mg / g, 1535.83 mg / g, and 1598.11 mg / g, which significantly exceeded the performance of pure Cu-BTC powder (393.60 mg / g). 2 The enhanced absorption can be attributed to the increase in the specific surface area and pore volume of the composite structure caused by the loading of Zif-8 onto the Cu-BTC surface. These additional binding sites contribute to the absorption of I 2 diffusion, improving the overall iodine absorption performance of the composite material and the internal interconnected pore network, thereby promoting I 2 Combination of adsorption capacity and fast adsorption kinetics.
[0098] Taking Example 3 as an example, after the adsorption experiment, the change from blue to dark brown in Example 3 was observed. Fig. 9 As shown in (A), it provides further evidence for the successful adsorption of iodine. The maximum gaseous iodine adsorption capacity of ZIf-8@Cu-BTC / 0.6 (1598.11 mg / g composite) significantly exceeds that of previously reported iodine adsorbent materials, such as Ag 0 Mordenite (Ag 0 Z) and some MOFs, which typically exhibit I of 100 mg / g-170 mg / g 2 This remarkable performance indicates that the composite material of the present invention has great potential in capturing iodine from a gaseous environment.
[0099] In order to study the iodine adsorption capacity in solution, adsorption kinetics experiments were carried out using standard iodine solution (1000 mg / L). Fig.10(a) The adsorption kinetic data shown show that in the initial stage, the adsorption capacity increases rapidly, and then increases at a slower rate until equilibrium is reached after 8 hours. The iodine adsorption capacity of the composite material of the present invention is significantly higher than that of pure Cu-BTC powder, and the ZIF-8 loading capacity is within a certain range, and the adsorption capacity of the composite material increases with the increase of the ZIF-8 loading capacity. Therefore, it is further preferred that the copper-based metal organic framework and the zinc nitrate hexahydrate mass ratio are 0.5 parts: 0.6 parts. After 8 hours, the iodine adsorption capacity of ZIf-8@Cu-BTC / 0.2, ZIf-8@Cu-BTC / 0.4, and ZIf-8@Cu-BTC / 0.6 are 336.82mg / g, 354.39mg / g and 373.90mg / g, respectively, and it is observed that the removal rate of ZIf-8@Cu-BTC / 0.6 is up to 85%. Embodiment Compared with pure Cu-BTC powder, the composite material shows that there is a synergistic effect between the two components. In addition, the unique structure of the composite material facilitates the recovery of the adsorbent, and the adsorption rate of the composite material of the present invention is significantly faster than that of the prior art ZIF-8@PU nanocomposite film (96 h).
[0100] To analyze the adsorption kinetics, pseudo first-order kinetic model, pseudo second-order kinetic model were applied, e.g. Fig.10 (c) The results show that the adsorption data best fits the pseudo first-order kinetic model, and the nonlinear correlation coefficient (R 2 ) values ranged from 0.982 to 0.995, which confirmed that the iodine adsorption process was controlled by the pseudo-first-order kinetic model. The adsorption data were consistent with the pseudo-first-order kinetic model. Compared with the pseudo-second-order kinetic model, the nonlinear correlation coefficient (R 2 ) values (0.982-0.995) were higher. After 12 h of reaction time, the adsorption capacities of Cu-BTC, ZIF-8 and their composites were 268.62 mg / g, 321.22 mg / g, 340.86 mg / g, 357.37 mg / g and 375.31 mg / g, respectively. This result confirms that the iodine adsorption process in our study is controlled by pseudo-first-order kinetics.
[0101] The adsorption isotherms of the embodiments and comparative examples were also studied. Fig.10 (b) shows the adsorption performance of the composite material synthesized by the present invention in absorbing iodine from an iodine / cyclohexane solution. This investigation is of great significance in nuclear waste management. Fig.10 As shown in (b), the adsorption capacity of the composite material obtained by the present invention from the solution is significantly better than that of the comparative example.
[0102] At low concentrations, the adsorption capacity increased with the increase in initial concentration, however, saturation was reached at higher concentrations and the adsorption process became concentration independent. Increasing the ZIF-8 loading in the composites further improved the adsorption capacity, and the Langmuir model provided a good fit for all the adsorption isotherms, such as Fig.10 The calculated maximum adsorption capacity increased from 265.61 mg / g for Cu-BTC to 660.73 mg / g for ZIf-8@Cu-BTC / 0.6, exceeding the literature reports in Table 1.
[0103] The effect of pH value in the range of 4-10 on iodine removal in water was studied, and the pH value was adjusted with HCl or NaOH solution, and the initial iodine concentration was fixed at 200 mg / L. Fig.11 As shown, the effect of pH on the removal efficiency was small, and the adsorption capacity remained well in the pH range of 4-10, indicating that weak acid and weak base conditions had no significant effect on the adsorption of iodine.
[0104] To evaluate the sustainability and long-term feasibility of the embodiments, a series of comprehensive adsorption-desorption cycles were performed using Example 3 as an example. Fig.12 As shown. The material was repeatedly exposed to iodine vapor and then subjected to a thorough regeneration process using ethanol, exposing 20 mg of sample to 20 ml of ethanol. Initially, the material exhibited an extremely high iodine capture capacity of 1598.11 mg / g, with a composite absorbance of 85.86% of iodine after the first and second elutions of iodine. Even after five cycles of adsorption and desorption, the capacity in the fifth cycle only slightly decreased to 1165.42 mg / g, which is 66.48% of the adsorbed amount. This sustained performance significantly exceeds that of commercially available zeolite-13X, which typically has a capacity range of 320-380 mg / g. The excellent regenerativeness and iodine capture capacity of ZIF-8@Cu-BTC strongly indicate its potential as a very promising material for addressing iodine-related environmental challenges.
[0105] In summary, the adsorption composite material obtained by the present invention has good adsorption capacity and water stability, and can fully adsorb iodine in a solution containing iodine ions or iodine element, and shows excellent performance in adsorbing iodine, which provides theoretical support for removing iodine from steam and liquid sources in practical applications.
[0106] It should be noted that the terms used in the present invention are only for describing specific embodiments, rather than limiting the scope of the present application. As shown in the present specification, unless the context clearly indicates an exception, the words "one", "a", "a kind of" and / or "the" do not specifically refer to the singular, but may also include the plural. The terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method or device. In the absence of more restrictions, the elements defined by the sentence "include one..." do not exclude the presence of other identical elements in the process, method or device including the elements.
[0107] It should also be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. Unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", etc. should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions of the embodiments of the present invention.
[0109] References: [1]Zhao Q, Zhu L, Lin G, Chen G, Liu B, Zhang L, et al. ControllableSynthesis of Porous Cu-BTC@polymer Composite Beads for Iodine Capture. ACSApplied Materials&Interfaces. 2019;11(45):42635-45. [2]Valizadeh B, Nguyen TN, Smit B, Stylianou KC. Porous Metal–OrganicFramework@Polymer Beads for Iodine Capture and Recovery Using a Gas‐SpargedColumn. Advanced Functional Materials. 2018;28. [3]Wang Z-W, Chen K-W, Gu A-T, Zhou X-Y, Wang P, Gong C-H, et al.Adsorption performance study of bismuth-doped ZIF-8 composites on radioactiveiodine in the vapor and liquid phases. Journal of Solid State Chemistry.2023;325:124186. [4]Liu L, Chen L, Thummavichai K, Ye Z, Wang Y, Fujita T, et al.Amino-functionalized MOF-on-MOF architectural nanocomplexes composed forradioactive-iodine efficient adsorption. Chemical Engineering Journal. 2023;474:145858. [5]Nenoff TM, Rodriguez MA, Soelberg NR, Chapman KW. Silver-mordenitefor radiologic gas capture from complex streams: Dual catalytic CH3Idecomposition and I confinement. Microporous and Mesoporous Materials. 2014;200:297-303. [6]Sava DF, Rodriguez MA, Chapman KW, Chupas PJ, Greathouse JA,Crozier PS, et al. Capture of volatile iodine, a gaseous fission product, byzeolitic imidazolate framework-8. Journal of the American Chemical Society.2011;133 32:12398-401. [7]Wang L, Chen P, Dong X, Zhang W, Zhao S, Xiao S, et al. PorousMOF-808@PVDF beads for removal of iodine from gas streams. RSC Advances.2020;10(73):44679-87. [8]Sava DF, Chapman KW, Rodriguez MA, Greathouse JA, Crozier PS, ZhaoH, et al. Competitive I2 Sorption by Cu-BTC from Humid Gas Streams. Chemistryof Materials. 2013;25(13):2591-6. [9]Assfour B, Assaad T, Odeh A. In silico screening of metal organicframework for iodine capture and storage. Chemical Physics Letters. 2014;610-611:45-9.
[10] Sun H, Mu P, Xie H, Zhu Z, Liang W, Zhou Z, et al. EfficientCapture and Reversible Storage of Radioactive Iodine by Porous Graphene withHigh Uptake. ChemistrySelect. 2018;3(36):10147-52.
[11] Xu L, Zheng Q, Wang Y, Jiang L, Jiang J, Qiu J. A pillareddouble-wall metal-organic framework adsorption membrane for the efficientremoval of iodine from solution. Separation and Purification Technology.2021;274:118436.
[12] Chen K, Wang P, Gu A, Djam Miensah E, Gong C, Mao P, et al. Core-shell Bi2S3 nanorods loaded ZIF-8 nanocomposites for efficient and reversiblecapture of radioactive iodine. Microporous and Mesoporous Materials. 2022;339.
[13] Liu S, Zeng Y, Liu J, Li J, Peng H, Xie H, et al. Efficientcapture and stable storage of radioactive iodine by bismuth-based ZIF-8derived carbon materials as adsorbents. Separation and PurificationTechnology. 2022;302:122151。
Claims
1. A ZIF-8@Cu-BTCMOF composite material, characterized in that: The structure of the ZIF-8@Cu-BTCMOF composite material is that a zinc-based metal organic framework is loaded on the surface of a copper-based metal organic framework.
2. The method for preparing the ZIF-8@Cu-BTCMOF composite material according to claim 1, characterized in that: The preparation method comprises: dissolving a copper-based metal organic framework, zinc nitrate hexahydrate and polyvinyl pyrrolidone (PVP) in methanol and mixing them evenly; adding a methanol solution containing 2-methylimidazole, stirring, solid-liquid separation, washing and drying.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the copper-based metal organic framework, zinc nitrate hexahydrate and polyvinyl pyrrolidone is 0.5 parts: 0.04 parts: 0.2 parts to 0.6 parts.
4. The preparation method according to claim 2, characterized in that: The mass ratio of the copper-based metal organic framework, zinc nitrate hexahydrate, and polyvinyl pyrrolidone is 0.5 parts: 0.04 parts: 0.6 parts.
5. The preparation method according to claim 2, characterized in that: The mass concentration of the copper-based metal organic framework in methanol is 0.5 g / 30 mL.
6. The preparation method according to claim 2, characterized in that: In the methanol solution containing 2-methylimidazole, the mass concentration of 2-methylimidazole is 0.54 g / 30 mL.
7. The preparation method according to claim 2, characterized in that: The volume ratio of the uniformly mixed solution to the methanol solution containing 2-methylimidazole is 1:
1.
8. The preparation method according to claim 2, characterized in that: The specific method of washing includes washing with methanol at least three times.
9. The preparation method according to claim 2, characterized in that: The drying temperature is 70°C-90°C.
10. Use of the ZIF-8@Cu-BTCMOF composite material according to claim 1 or the ZIF-8@Cu-BTCMOF composite material obtained by the preparation method according to any one of claims 2 to 9 in adsorbing iodine.
Citation Information
Cited By
Cu / Zn bimetal organic framework catalyst and application thereof
CN120485864A
Preparation method and application of amino acid metal cation adsorption material
CN122321808A
